Embracing the Evaporative System in Air Conditioning Technology for Efficient Cooling Solutions - Gde Widiantara, Ida Bagus; Negara, I Gede Artha; Bangse, Ketut (INVOTEK: Jurnal Inovasi Vokasional dan Teknologi, 2024)
The use of an air conditioning system requires large amounts of electrical energy to carry out repeated vapor compression cycles. The use of an evaporative cooling system in this research is by spraying condensate water on the condenser, which is one solution to absorb condenser heat. Another thing that can be done is to reset the fan speed on the condenser to cool it. Resetting the fan speed on the condenser can also help improve AC performance and reduce electrical energy use. The test was carried out by modifying the 1 Pk R-410a AC split condenser by installing 6 nozzles, 2 rows of 3 columns and a DC pump to spray water on the condenser. The independent variables of this research are spraying position and fan speed. The result obtained from the research is an increase in COP by 35% and a reduction in electrical power usage by 15% by using additional water spray with a nozzle behind the condenser both when blowing the full blower and when the blower blowing speed is reduced by 75%. The use of evaporative systems in air conditioning technology is a promising solution to achieve sustainable and efficient cooling solutions.